Islamic Education Strategic Planning: Building Schools with Character and Global Competitiveness - Rifki, Ahmad; Januar, Januar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Strategic planning in Islamic education is an important approach to building schools that are able to integrate Islamic character values with global competencies. With the challenges of globalization and technological advancement, Islamic education must respond with strategies that involve the use of information technology and strengthening character education. Studies show that this approach can improve the competitiveness of schools both locally and internationally. Strengthening character through an Islamic values-based curriculum allows schools to not only produce students who excel academically, but also have high moral and spiritual integrity. The implementation of appropriate strategies such as curriculum innovation and collaboration with international institutions can create globally competitive schools and sustainably prepare students to face an increasingly complex world.